Case report: Traumatic lingual hematoma. (April 2019) - Massey, B.; Juhasz, K.; Licata, J.; Schell, S.; English, G.
Abstract: We describe a case of traumatic lingual hematoma in a patient on dual antiplatelet therapy. After securing the airway, bilateral lingual artery embolization successfully halted expanding hematoma formation. Patient subsequently required tracheostomy for continued airway edema. Although patient course was wrought with postoperative complications, we review this case to illustrate how prompt hematoma evacuation and embolization can resolve significant vasovagal bradycardia and hypotension secondary to expansile lingual hematoma.